Employment Opportunities & Retention for Women in Information Technology Sector - Kumar, Ravindra; Agarwal, Himanshu (Journal of Commerce and Trade, 2020)
The aim of this research is to examine the Employment Opportunities and Retention for Women in I T Sector. Data from 100 women employees has been collected from IT companies situated in Noida. The study employs qualitative and quantitative research techniques which involves the use of self-structured questionnaires and statistical techniques as T-test, descriptive analysis, Regression analysis and Cronbach’s alpha. Present study reveals that decision of stay with the organisation. Marital status of a women employee does not affect her decision to stay in job. Work life balance and job security are the other reasons of looking for new job by women employees. Since the data has been collected form IT companies situated in Noida, the ability of the data to represent the entire population is reduced. The results of this study will provide insights to implement strategies to increase women employee retention in IT companies and employment opportunities. Classification-JEL : L52, O14